Knockdown of LMX1B Suppressed Cell Apoptosis and Inflammatory Response in IL-1β-Induced Human Osteoarthritis Chondrocytes through NF-κB and NLRP3 Signal Pathway. (12th September 2022) - Mu, Yiping; Wang, Lining; Fu, Ling; Li, Qi
Abstract : Osteoarthritis (OA), a chronic degenerative joint disease, always occurred in the aging population. There is evidence suggests that chondrocytes' survival, inflammation, and apoptosis play critical roles in OA pathogenesis. LMX1B has been shown to be involved in antiosteogenic function in early patterning of the calvaria. However, the role and mechanism of LMX1B in OA is not unknown. The present study observed that LMX1B was highly expressed in OA patients compared with normal patients. Besides, we found that IL-1 β increased LMX1B mRNA and protein expression in SW1353 and C28/I2 chondrocytes. LMX1B knockdown increased IL-1 β -induced cell viability and proliferation and suppressed cell apoptosis and inflammation response, including IFN- γ, TNF- α, IL-6, prostaglandin E2 (PGE2), and NO both in SW1353 and C28/I2. Furthermore, LMX1B silence inhibited MMP-3 and MMP-13 expression both in SW1353 and C28/I2 cells. Also, the activation of the NF- κ B and NLRP3 signaling pathway was suppressed in LMX1B silence cells by decreasing the p-p65 and NLRP3 protein expressions. Additionally, inhibition of NF- κ B by PDTC suppressed NLRP3 expression. Moreover, NLRP3 overexpression reversed the effects of LMX1B silence on chondrocytes' survival, proliferation, apoptosis, and inflammation. Finally, we confirmed that LMX1B depletion had protective effects in OA rats in vivo .